Calcule: 7- (-20) =
18 - (+17) =
18 + (-17) =
18 - (-17) =
0 - (+3) =
Soluções para a tarefa
Respondido por
2
7 - (-20) = 7 + 20 = 27
18 - (+17) = 18 - 17 = 1
18 + (-17) = 18 - 17 = 1
18 - (-17) = 18 + 17 = 35
0 - (+3) = 0 - 3 = -3
Espero ter ajudado.
18 - (+17) = 18 - 17 = 1
18 + (-17) = 18 - 17 = 1
18 - (-17) = 18 + 17 = 35
0 - (+3) = 0 - 3 = -3
Espero ter ajudado.
Respondido por
1
Regras de sinal:
" - " com " - " = "+"
" - " com "+" = " - "
" + " com " - " = " - "
" - " com " - " = " + "
a)
= 7- (-20)
= 7 + 20
= 27
¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨
b)
= 18 - (+17)
= 18 - 17
= 1
¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨
c)
= 18 + (-17)
= 18 - 17
= 1
¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨
d)
= 18 - (-17)
= 18 + 17
= 35
¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨
e)
= 0 - (+3)
= 0 - 3
= - 3
¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨
" - " com " - " = "+"
" - " com "+" = " - "
" + " com " - " = " - "
" - " com " - " = " + "
a)
= 7- (-20)
= 7 + 20
= 27
¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨
b)
= 18 - (+17)
= 18 - 17
= 1
¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨
c)
= 18 + (-17)
= 18 - 17
= 1
¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨
d)
= 18 - (-17)
= 18 + 17
= 35
¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨
e)
= 0 - (+3)
= 0 - 3
= - 3
¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨¨
Perguntas interessantes